FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI KOPI ARABIKA DI LMDH KARAMAT JAYA KECAMATAN CISURUPAN KABUPATEN GARUT - Nadila Indarwati; Ahmad Choibar Tridakusumah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Karamatwangi village is one of the coffee-producing centers in The Cisurupan Garut District. Arabica coffee production in this village should be highlighted, especially they are well known in national and international markets. Problems faced by coffee farmers include in terms of providing quantity to meet the needs of the international market. The purpose of this study was to analyze the factors that affect Arabica coffee production in LMDH Karamat Jaya. The design of this study uses a quantitative design with survey research techniques, the respondents of this study are coffee farmers led karamat Jaya members and use analysis of Multiple Linear Regression. The results of multiple linear analyses obtained urea fertilizer, the number of plants, and labor as the most influential production factor to production. Other factors that do not have much effect on arabica coffee production are land area, manure, plant age, and capital.